Managing back pain - Roth, Patrick, 1960-; Ross, Phil (Philip G.) (--For dummies., 2026)
"Looking for a way to reduce and manage your back pain without unnecessarily relying on addictive pain medications? In Managing Back Pain For Dummies, an experienced neurosurgeon and a renowned personal trainer team up to walk you through the steps to lessen pain and discomfort with accessible, evidence-based treatments. You'll learn about everything from exercises you can do yourself at home to more complicated therapies, like nerve blocks and injections. This up-to-date guide is a comprehensive, reliable guide for anyone with back pain."--